A Review on Medicinal Effects of Abelmoschus esculentus on Type 2 Diabetes (Asian Journal of Pharmaceutics (AJP), 2026)
Abelmoschus esculentus (L.), or okra or lady finger, is an extensively used vegetable that has strong healing powers in the treatment of type 2 diabetes mellitus. Its bioactive substances, especially flavonoids, polyphenols, and mucilage, have hypoglycemic, antioxidant, and anti-hyperlipidemic activities. This review provides a summary of the existing evidence on the mechanism of action of okra as an antidiabetic agent, involving the regulation of diabetic metabolism, promotion of insulin sensitivity, and inhibition of oxidative stress-induced pancreatic injury. Besides, the review highlights the pharmacological research, clinical significance, and future potential of using A. esculentus as a natural adjunct agent in diabetes treatment.